Variasi Pertumbuhan Manglid (Manglietia glauca Bl.) sebagai Sumberdaya Hayati Lokal di Tiga Lokasi - Sugeng Pudjiono; Mudji Susanto; Mashudi Mashudi; Ratna Adji Hartati (Universitas Sebelas Maret, 2018)
Manglid is one of the rare local biological resources of forest tree species. Manglid is potential producer of wood for carpentry. The purpose of the research is to know the growth variations of Manglid in 3 locations. The design that is used is by planting Manglid in the form of demonstration plot in three locations; Purwobinangun, Sleman Regency, Yogyakarta Province; Candiroto, Temanggung Regency, Central Java Province; and Dompyong, Trenggalek Regency, East Java Province. The Manglid seedlings are came from West Java Province including Tasikmalaya Regency, Sukabumi Regency and Sumedang Regency. The growth characters that are observed include the height of the plant, the diameter of the rod, and the percentage of life at the age of 12 months after planting. The results showed that there is a difference between the growth of plants in 3 different locations. The height of Manglid planted in Purwobinangun Sleman Regency is 45-296cm with 139cm in average, the diameter of the rods is 0.59-5.15 cm and 2.73cm in average, the life percentage is 90-100% with average 98%. Then in the Candiroto, Temanggung Regency the height of Manglid is 10-379cm with 191cm in average, the diameter of the rods is 0.37-9.68 cm and 4.14cm in average, the life percentage is 40-90% with average 65.73%. While in Dompyong, Trenggalek Regencythe height of Manglid is 20-229cm with 113.6cm in average, the diameter of the rods is 0.3-4.0cm and 1.3cm in average, and the life percentage is 55-100% with 85,3% in average.